Richard Strauss in context - Kristiansen, Morten 1968-; Jones, Joseph E. 1978- (Composers in context, 2020)
Richard Strauss in Context offers a distinctive approach to the study of a composer in that it places the emphasis on contextualizing topics rather than on biography and artistic output. One might say that it inverts the relationship between composer and context. Rather than studies of Strauss's librettists that discuss the texts themselves and his musical settings, for instance, this book offers essays on the writers themselves: their biographical circumstances, styles, landmark works, and broader positions in literary history. Likewise, Strauss's contributions to the concert hall are positioned within the broader development of the orchestra and trends in programmatic music. In short, readers will benefit from an elaboration of material that is either absent from or treated only briefly in existing publications. Through this supplemental and broader contextual approach, this book serves as a valuable and unique resource for students, scholars, and a general readership